Sexuality and the "˜Relations of Ruling': Using Institutional Ethnography to Research Lesbian and Gay Foster Care and Adoption - Stephen Hicks (Social Work and Society)
This article makes use of institutional ethnography to research foster care and adoption by lesbians and gay men, drawing on the work of the feminist sociologist Dorothy E. Smith in order to demonstrate the investigation of social work institutional categories and the "˜relations of ruling'. Through an analysis of the ways in which 'gender' and the idea of the 'gender role model' is used within the assessment of gay and lesbian foster carers and adopters, the author shows how these categories are produced and used to police relationship forms and to identify "˜deviant instances'.